2003
DOI: 10.1016/s0925-8388(03)00035-5
|View full text |Cite
|
Sign up to set email alerts
|

Stress-induced diffusion of hydrogen in metallic membranes: cylindrical vs. planar formulation. I

Abstract: The hydrogen chemical potential in metallic membranes is affected by the self-stresses generated by the interstitial transport within the lattice (stress-induced diffusion). This article provides analytical and numerical evidence that, in the presence of stress-induced diffusion, hydrogen transport in thin metallic cylindrical membranes can exhibit macroscopic features qualitatively different from those observed in planar structures. This is a consequence of the different ways diffusion-induced stresses propag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 29 publications
2
14
0
Order By: Relevance
“…(5) and (6) that both in the ␣ and ␤ phases the hydrogen flux is proportional to the concentration gradient. Therefore, in cylindrical geometry, even in the presence of stress-induced diffusion, the flux expression is strictly Fickian, whereas in the planar case, a non-local integral contribution to hydrogen flux is also present [10][11][12][13][14]. Consequently, the role of self-stresses in tubular membranes is solely that of increasing the effective (concentration dependent) diffusion coefficient both in the ␣ and in the ␤ phases.…”
Section: The Cylindrical Casementioning
confidence: 99%
See 3 more Smart Citations
“…(5) and (6) that both in the ␣ and ␤ phases the hydrogen flux is proportional to the concentration gradient. Therefore, in cylindrical geometry, even in the presence of stress-induced diffusion, the flux expression is strictly Fickian, whereas in the planar case, a non-local integral contribution to hydrogen flux is also present [10][11][12][13][14]. Consequently, the role of self-stresses in tubular membranes is solely that of increasing the effective (concentration dependent) diffusion coefficient both in the ␣ and in the ␤ phases.…”
Section: The Cylindrical Casementioning
confidence: 99%
“…In previous papers, Adrover et al [12][13][14] and Zhang et al [10,11] have made use of the SJD model to analyze the occurrence of the uphill-diffusion in planar and tubular Pd membranes, for hydrogen contents falling within the ␣ phase composition range. These authors have shown that: (i) the SID model does not display any non-local contribution to the flux in a cylindrical membrane; but (ii) the uphill effect occurs as a direct consequence of the non-linear, non-local, time-dependent boundary conditions, corresponding to a permeation experiment.…”
Section: The "Uphill-diffusion" Effectmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, the usefulness of these equations for modelling of experimental data and their quantitative interpretation is really limited [8,30,45,46]. Later on, for the discussed transport even more complex models have been also proposed [49][50][51].…”
Section: Diffusion Coefficient Of Hydrogenmentioning
confidence: 99%